Heat transfer analysis in compact heat exchanger with fibre reinforced plate - Hamood, M; Oumer, A. N.; Azizuddin, Abd Aziz; M., Ishak; Siregar, J. P.; Mamat, O (IOP Publishing, 2021)
Due to their lightweight and ease of manufacturing, fibre-reinforced composites are replacing metals in many heat exchanger applications. However, their heat transfer dissipation performance is not investigated in detail. This paper aims to study experimentally the heat transfer performance of fins made from fibre reinforced composites in compact heat exchangers. Thin fins were manufactured from reinforced fibre composites by the hot pressing technique. The fins have dimensions of 11.5 cm wide and 11.5 cm long. Five different airflow velocities with fixed water flow rates were considered in the analysis. The temperature distribution inside the tube was measured at eight different points using a K-type thermocouple. The results showed that the water temperature at the outlet section was the highest at the lowest airflow velocity. Moreover, the air-side heat transfer coefficient increased along the tube length at all airflow velocities. The comparable heat transfer performance results make the fibre reinforced fins a good choice in the compact fin-and-tube heat exchanger.